3D heterogeneous ZnCo2O4@NiMoO4 nanoarrays grown on Ni foam as a binder-free electrode for high-performance energy storage. (December 2020) - Wang, Jing; Wang, Shen; Tian, Ye; Jin, Xiangyang; Dong, Jing
Highlights: Heterogeneous ZnCo2 O4 @NiMoO4 core-shell nanoarrays directly grown on the Ni foam. The electrode shows high specific capacitance 1912 F g −1 at 1 A g −1 and good rate capability 55%. A solid-state device was fabricated with high energy density 57.5 Wh∙Kg −1 and power density 18000 W∙Kg −1 . The potential window of this device can be stabled from 0 V to 1.8 V. Abstract: 3D heterogeneous ZnCo2 O4 @NiMoO4 core-shell nanowire/nanosheets nanoarrays (3D ZnCo2 O4 @NiMoO4 NAs) grown on the conductive Ni foam substrate was successfully synthesized by a two-step simple water bath heating method. The prepared composites were characterized by XRD, FESEM, and TEM and were found to ZnCo2 O4 nanowires acted as the core and the NiMoO4 nanosheets covered as the shell. Using as a supercapacitor electrode, 3D ZnCo2 O4 @NMioO4 NAs/Ni foam demonstrate a high specific capacitance 1912 F g −1 (at the current density of 1 A g −1 ) and excellent rate capability (55% initial capacity retention at 20 A g −1 ). Furthermore, the asymmetric supercapacitors constructed with the anode (carbon nanotubes/Ni foam) and the cathode (3D ZnCo2 O4 @NiMoO4 NAs/Ni foam) exhibit excellent performances in energy storage. This solid-state device shows high specific energy 57.5 Wh∙Kg −1 (at specific power density of 900 W∙Kg −1 ) and high specific power 18000 W∙Kg −1 (at specific energy of 30 Wh∙Kg −1 ) by broaden the potentials range from 0 V to 1.8 V. These superior results of 3D ZnCo2 O4 @NiMoO4 NAs mainly comes from the synergistic effect of 3D array microstructure of the conductive ZnCo2 O4 /Ni foam and the nanosheet structure of NiMoO4. The ZnCo2 O4 /Ni foam can provide facial routes for the transfer of the ions and electrons and the nanosheet structure is benefit for the intercalation-deintercalation processes of OH − ions in the NiMoO4 . This work provides a new strategy for the preparation of high-performance supercapacitor electrode.